Winning Ways or Winning Weighs: Obtaining a SSHRCC Doctoral Fellowship - Wall, G.; Frideres, J. S. (Canadian Journal of Higher Education, 1993)
Over the past decade there has been a dramatic increase in the number of students applying to graduate school and as the cost of education continues to escalate, more students have been applying for external funding such as SSHRCC doctoral fellowships. Over time, guidelines for assessing applications have been established by the various SSHRCC committees in order to decide which applicants will be successful. The present research identifies the qualifications of applicants which are related to obtaining a SSHRCC doctoral fellowship. One hundred fourteen applications were randomly selected for analysis. A variety of information from the application, e.g., thesis proposal, letters of recommendation, schools attended, publications, was coded and subjected to multivariate analysis. The results show that a high degree of unanimity was evident among assessors. Referee appraisals and the rank provided by the department are important in deciding whether a student is recommended for a SSHRCC fellowship. Publications and other academic awards play a lesser but significant role in the decision-making process. The results also suggest that gender and participation in the labour force are potentially important variables in determining an applicant's success in obtaining a fellowship.